Kajian Wacana Kritis Teun A. Van Dijk pada Akun Instagram @komikfaktap Periode 2024 - Andhika, Asagi Mukti Nur; Muharudin, Eko; Sukirno, Sukirno; Suroso, Eko (Ruang Kata, 2025)
This study examines how social inequality is represented in Instagram digital comics @komikfaktap throughout 2024. Using Teun A. van Dijk's Critical Discourse approach, this study seeks to understand not only the messages in text and images, but also the way comics shape, influence, and strengthen the social meaning of their readers. Comics were chosen purposively because they contain social issues that reflect the dynamics of politics, economy, education, and power relations that are close to the daily experience of society. This research uses a descriptive qualitative method. Data was obtained through a purposive sampling technique on digital comic uploads on @komikfaktap's Instagram account, which was collected through documentation in the form of screenshots and recording supporting information. The data were then analyzed by paying attention to the structure of the discourse (macrostructure, microstructure, and superstructure), social cognition, and social context according to Teun A. van Dijk's framework. The findings of the study show that most of the comics (55.6%) highlight the inequality of democracy and political practices. Others discussed economic policies (22.2%), stagnant education situation (11.1%), and various forms of international dominance (11.1%). The results of the analysis showed that the comics used humor, visual metaphors, and symbols that were easily recognizable, so that the social criticism conveyed felt light but still sharp. In terms of social cognition, comics make use of the reader's collective memory and life experiences, making the criticism displayed not only entertainment, but also reflection. In a broader social context, comics serve as an alternative space in providing the public with an opportunity to see the power structures at work in everyday life. The results of this study show that digital comics not only function as an entertainment medium, but also as a means of critical literacy that is able to reach a wide audience quickly and effectively. Follow-up research can broaden the focus to help shape the power of disseminating critical discourse on social media